Метод потенціалу в граничних задачах для процесів з незалежними приростами - Братійчук, М.С. (Український математичний журнал, 2015)
Предложен новый подход к использованию метода потенциала Королюка при исследовании граничных функционалов для процессов с независимыми приращениями. Получены формулы для совместного распределения функционалов, связанных с достижением процессом уровня, и проведен их асимптотический анализ. Изучена возможность пересечения процессом уровня непрерывным образом. We propose a new approach to the application of the Korolyuk potential method for the investigation of limit functionals for processes with independent increments. The formulas for the joint distribution of functionals related to crossing a level by the process are obtained and their asymptotic analysis is performed. The possibility of crossing a level by the process in a continuous way is also investigated.